2021
DOI: 10.1097/bot.0000000000001988
|View full text |Cite
|
Sign up to set email alerts
|

Intentional Temporary Limb Deformation for Closure of Soft-Tissue Defects in Open Tibial Fractures

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
0
17
0
1
Order By: Relevance
“…These include acute shortening, primary shortening, acute deformation, angular shortening, intentional temporary deformation, intentional deformation, intentional temporary shortening and deformation, shortening with angulation and rotation, etc. 9 , 11 , 12 , 14 , 18 , 24 , 26 , 27 , 32 34 We propose the above-mentioned terms can be replaced by one term, “Artificial Deformity Creation” or ADCr, which can include techniques of shortening, angulation and rotation either separately or in combination.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These include acute shortening, primary shortening, acute deformation, angular shortening, intentional temporary deformation, intentional deformation, intentional temporary shortening and deformation, shortening with angulation and rotation, etc. 9 , 11 , 12 , 14 , 18 , 24 , 26 , 27 , 32 34 We propose the above-mentioned terms can be replaced by one term, “Artificial Deformity Creation” or ADCr, which can include techniques of shortening, angulation and rotation either separately or in combination.…”
Section: Discussionmentioning
confidence: 99%
“…Four authors 15 , 22 24 have suggested, for a one-step acute shortening, a specific value of 3 cm. Three authors 25 27 propose to base the decision on the state of soft tissues and the vascular status of the injured limb, as well as on the results of pulse oximetry and intraoperative Doppler sonography. According to Atbasi et al and Hernández-Irizarry et al, the criterion for the limit of acute shortening is the beginning of changes in Doppler and pulse oximetry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these settings, surgeons have to find innovative ways of using available technology and consumables to circumvent the lack of resources that may be readily available in high-income countries (HICs) [ 1 ]. One such example is deformity-assisted wound closure to manage open fractures with skin loss to compensate for the lack of plastic and micro-vascular surgical capabilities ( Figure 1 ) [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%